Resocjalizacja poprzez naukę w oparciu o teorię wartości w warunkach izolacji penitencjarnej - Monika Kaczmarczyk; Milena Drąg (Edukacja Ustawiczna Dorosłych)
The authors discuss a rarely raised topic concerning the role of education in life in penitentiary isolation. Basic issues of education, learning, and social rehabilitation against the background of classical rehabilitation pedagogy. The authors present the axiological concepts and the concepts of rehabilitation. The situation of people in isolation arouses significant interest. Awareness of the high rate of recidivism indicates that, in addition to rehabilitation through therapy and work, auxiliary institutions such as prison schools should also play an important role. It is education that allows many of the basic needs of incarcerated people to be met, thus giving them the opportunity for a better start, once they leave prison.